Feel-Own-Move: a psychomotor therapy program for victims of intimate partner violence living in shelter homes. Feasibility and effects on mental health, bodily dissociation, and quality of life - Machorrinho, Joana; Marmeleira, José; Veiga, Guida; Santos, Graça Duarte (Frontiers in Psychology, 2023)
Intimate partner violence (IPV) is a worldwide concern, impacting victims’ mental health, physical health, and quality of life. High rates of posttraumatic stress disorder (PTSD), depression, anxiety, bodily dissociation, and somatic symptoms have been found in victims of IPV, with an important impact on the chronicity of impairments and on the outcomes of psychological interventions. Therapeutic interventions available in shelter homes for victims are scarce in addressing their body-mind needs, therefore asking for better empirical research. Thus, the aim of this study was to evaluate the feasibility and effects of Feel-Own-Move (FOM), an 8-week psychomotor therapy program for victims of IPV, on their mental health, levels of bodily dissociation, and general quality of life. A within-subject repeated measures design was used to evaluate the intervention effects, and feasibility results were analyzed. Seventeen women completed the program (mean age 42.8 years, range 21-64). Results showed a significant decrease in levels of bodily dissociation, with FOM having a large effect size. The intervention also had a large effect size at increasing the environment domain of quality of life, although no statistically significant differences were found. FOM ended with excellent rates of reach, adherence, acceptability, and satisfaction. A positive retention rate was also found. In conclusion, FOM seems to be a feasible psychomotor therapy intervention for female victims of IPV living in shelters. Importantly, this program showed to be effective in reducing bodily dissociation among participants, which is suggested to prospectively contribute to their mental health and quality of life.